CURRENT DATA ON DIGESTIVE FUNCTIONAL DISORDERS IN INFANTS - M. I. Dubrovskaya (Вопросы современной педиатрии, 2013)
The article deals with the terminology, classification, etiology and pathogenesis of the most common digestive functional disorders in infants. The causes of digestive functional disorders are closely related to the anatomical and physiological peculiarities, child’s growth, gradual maturing of the neural regulation and motoric function of the digestive tract and the sphincters, as well as to its morpho-functional immaturity. Coupled with motor-evacuation dysfunction and neural disorders (mainly of the hypoxemic etiology) these factors lead to abdominalgia and dyspepsia. Appropriate treatment and prophylaxis in infants, including special diet regimens and recommendations, as well as psychological correction of children-parental relationships, allow to prevent development of chronic disorders of the digestive tract in future life.